Role of Bleach Sedimentation Technique for the Diagnosis of Tuberculosis. - Sarker, Md Mahbur Rashid; Farooq, Md Shamim; Roy, Chandan Kumar; Hassan, Parvez (KYAMC Journal, 2017)
Tuberculosis remains a major threat to world health. The main aim of this study was to improve the microscopic detection of AFB from sputum by Bleach sedimentation technique using household bleach. This was a cross sectional type of study conducted for a period of one year from July 2010 to June 2011 in the Department of Laboratory Services, Khwaja Yunus Ali Medical College Hospital (KYAMCH), Sirajgonj. A total of 115 clinically suspected tuberculosis patients aged between 7-85 years were included in the study. Among them 35 (30.4%) patients had TB positive by routine (Direct microscopy) method; whereas, by bleach concentration method 42 (36.5%) were found positive; diagnosing 07 additional patients. The rise of 16.7% in sputum positivity by bleach sedimentation microscopy over the direct smear microscopy was found to be statistically significant (p= <0.005). Paired samples t test analysis of sputum showed a significant correlation between this two methods (r=0.896, p <0.001). This study suggests that Bleach sedimentation method is better than direct conventional method. So it should be applied to all laboratories across the country because it is cheap early available and also safety to the laboratory staffs. KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 497-502